The Effect of Sodium Selenite and Vitamin A on FSH and LH Level in Albino Male Mice treated with Hexavalent Chromium (Baghdad Science Journal, 2014)
The present expermint was designed to determine the effect of Sodium Selenite (0.5 mg/kg) and Vitamin A (10 mg/kg) in FSH and LH level in Albino Male Mice treated with Hexavalent Chromium (1000 ppm). `This study included 48 mice divided into six groups (1st group treated with distilled water and the 2nd group treated with Sesame Oil were considered as control group, 3th group exposed to Hexavalent chromium , 4th group treated with Sodium Selenite and exposed to Hexavalent Chromium , 5th group treated with Vitamin A and exposed to Hexavalent Chromium and 6th group treated with Sodium Selenite and Vitamin A and exposed to Hexavalent Chromium ) . The treatment lasted for 35 days. The results showed a significant (P ? 0.05) decrease in FSH and LH levels in 3rd group that exposed to Hexavalent Chromium as compared with two control groups. The results of the group that treated with Sodium Selenite and exposed to Hexavalent Chromium showed a significant (P ? 0.05) increase in FSH and LH levels as compared with group that exposed to Hexavalent Chromium. The group treated with Vitamin A and exposed to Hexavalent Chromium revealed significant (P ? 0.05) increase in FSH and LH levels when compared to the group exposed to Hexavalent Chromium . The last group that treated with Sodium Selenite and Vitamin A and exposed to Hexavalent Chromium showed a significant (P ? 0.05) increase in FSH and LH levels as compared to the group that treated with Sodium Selenite and exposed to Hexavalent Chromium and to group that treated with Vitamin A and exposed to Hexavalent Chromium. From the present study it could be concluded, that Sodium Selenite and Vitamin A have a positive effect on fertility in Albino Male Mice that treated with Hexavalent Chromium by either affecting the FSH and LH hormones level or by eleminate the negative effect of Hexavalent Chromium